Association of Serum Hepatic Enzyme Level With Metabolic Syndrome in Adult Bangladeshi Population (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: The Metabolic Syndrome (MetS) is now considered as global pandemic. According to the findings from literature data, increased hepatic enzymes may serve as useful indicators of MetS, but there is inconsistency in the results.  Current research is designed to determine the association between serum hepatic enzyme level with MetS in adult Bangladeshi population and to find out whether altered hepatic enzyme level can be used as potential biomarker for early detection of MetS.  Materials and methods: This analytical cross-sectional study included 50 subjects with MetS from Chittagong Medical College Hospital between January 2022 to December 2022. Fifty apparently healthy subjects who did not fulfilled the MetS criteria were selected for Control group. We used the modified National Cholesterol Education Program Adult Treatment Panel III criteria to diagnose MetS. Serum concentrations of Alanine Aminotransferase (ALT) Aspartate Aminotransferase (AST) Alkaline Phosphatase (ALP) and  g-glutamyl transferase (GGT) were measured and compared between groups.Results: The participants with MetS had significantly higher mean ALT, AST, ALP and GGT levels than the non Mets control group. The mean AST/ALT ratio was 0.67±0.19 and 0.82±0.12, respectively, in participants with and without MetS (p